The relationship between serum histon levels and the severity of acute pancreatitis - Biberci Keskin, Elmas; Tüzün İnce, Ali and Sümbül Gültepe, Bilge and Hakkı Köker, İbrahim and Şentürk, Hakan (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Despite various scoring systems and imaging methods, it is hard to predict the severity and the course of acute pancreatitis (AP), thereby necessitating better and more reliable markers. Since inflammation plays a key role in the pathogenesis of AP, we sought to determine whether histone, which is a novel inflammatory marker, may play a role in the prediction of severity and prognosis. Materials and Methods: A total of 88 consecutive adult patients (>18 years) with a first AP episode were prospectively enrolled in the study. Severe AP was defined as having a revised Atlanta score >3 in the first 48 h after admission. Circulating histone 3 and 4 levels were measured using the enzyme-linked immunosorbent assay method. Results: Eighty-eight consecutive adult patients with a first episode of AP were divided into two groups according to severity, in which 56 (63.6%) were assigned to the mild AP group and 32 (36.4%) to the severe AP group. White blood cell, hemoglobin, creatinine, and aspartate aminotransferase levels were significantly higher in the severe AP group. However, there was no difference in serum histone levels between the groups, and there was no correlation between revised Atlanta score and serum histone levels either. Conclusion: Serum histone levels did not significantly differ between the severe and mild AP groups. Therefore, these markers may not provide additional benefit for determining the severity of AP.